THE PHILOSOPHICAL ANALYSIS OF FLORA AND HUMAN ISSUES IN THE SPIRITUAL AND ETHICAL HERITAGE OF MAHMUD AL-ZAMAKHSHARI - Adilov Zafar Yunusovich (Scholars Digest Publishing, 2024)
This piece provides a comprehensive overview of the essential role that water plays in maintaining human health. It begins with a scientific definition of water, highlighting its chemical composition and significance in biological systems. The benefits of water for the human body are explored in detail, emphasizing its involvement in various physiological processes such as digestion, temperature regulation, cellular function, and detoxification. The annotation underscores the importance of adequate hydration in preventing health complications such as dehydration, kidney stones, and impaired cognitive function. The conclusion reinforces the idea that water is vital for overall well-being and stresses the need for individuals to prioritize regular water intake as part of a healthy lifestyle. This work serves as a reminder of the fundamental role water plays in maintaining the proper functioning of the human body and the prevention of preventable health issues.
Keywords: Mahmud al-Zamakhshari, Arabic grammar, theology, Islamic Etiquettes of Drinking Water, society.